2018
DOI: 10.1039/c8nr01516c
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the role of substrate stiffness in enhancing the internalization efficiency of plasmid DNA in stem cells using lipid-based nanocarriers

Abstract: This study investigates the role of substrate stiffness on non-viral transfection of human adipose-derived stem cells (hASCs) with the aim to maximize hASCs expression of vascular endothelial growth factor (VEGF). The results confirm the direct effect of substrate stiffness in regulating cytoskeletal remodeling and corresponding plasmid internalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 35 publications
(34 reference statements)
0
19
0
Order By: Relevance
“…BMP-2 transgene expression was significantly increased on 670 kPa versus 10 kPa hydrogels (2-fold increase), corresponding with an observed 6-fold significant increase of polyplex internalization. In comparing soft versus stiff substrates, Modaresi et al [120] tested delivery of pDNA encoding for vascular endothelial growth factor (VEGF) complexed with LF2000, to hAMSCs cultured on 0.5 or 32 kPa poly(dimethylsiloxane) PDMS surfaces coated with 1% ( w / v ) gelatin. VEGF transgene expression was significantly higher (4.5-fold) in hAMSCs cultured on 32 kPa versus 0.5 kPa PDMS, which correlated to a 2.5-fold significant increase in lipoplex internalization, which was shown to be correlated with increased caveolae-mediated endocytosis.…”
Section: Recent Approaches To Improve Nonviral Gene Delivery To Mscsmentioning
confidence: 99%
“…BMP-2 transgene expression was significantly increased on 670 kPa versus 10 kPa hydrogels (2-fold increase), corresponding with an observed 6-fold significant increase of polyplex internalization. In comparing soft versus stiff substrates, Modaresi et al [120] tested delivery of pDNA encoding for vascular endothelial growth factor (VEGF) complexed with LF2000, to hAMSCs cultured on 0.5 or 32 kPa poly(dimethylsiloxane) PDMS surfaces coated with 1% ( w / v ) gelatin. VEGF transgene expression was significantly higher (4.5-fold) in hAMSCs cultured on 32 kPa versus 0.5 kPa PDMS, which correlated to a 2.5-fold significant increase in lipoplex internalization, which was shown to be correlated with increased caveolae-mediated endocytosis.…”
Section: Recent Approaches To Improve Nonviral Gene Delivery To Mscsmentioning
confidence: 99%
“…51,72,73 Besides providing localized delivery, scaffolds can also be tuned to manipulate the extent and even the location of uptake within cells. 74 This can be achieved by altering the physico-chemical properties (elasticity, topology, composition, etc.) of the substrate, which the cells are attached to, thereby regulating cytoskeletal remodelling 75 and subsequently internalization pathways 74 (Figure 2 and Table 1).…”
Section: Tissue-localized Deliverymentioning
confidence: 99%
“…It was previously reported that the surface properties of biomaterial, including composition, 47 stiffness, 48 topography 49 and so on, could affect cytoskeletal rearrangement, thereby influencing its cellular endocytosis. 50 In order to investigate whether the photothermal properties of the composite coating could lead to cytoskeletal rearrangement, we have used the laser confocal microscope for this study.…”
Section: Effects Of Visible-light Illumination On Cellular Endocytosis Of Lf/gfpmentioning
confidence: 99%